1995
DOI: 10.1111/j.1346-8138.1995.tb03918.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Atrophoderma of Pasini and Pierini: Analysis of Glycosaminoglycan of the Lesional Skin

Abstract: We report a case of atrophoderma of Pasini and Pierini. We determined the glycosaminoglycan content in the involved skin. Dermatan sulfate content in the involved skin (1.88 micrograms uronic acid/mg dry skin) was greater than that in the uninvolved skin (1.05 micrograms uronic acid/mg dry skin). No significant differences in hyaluronic acid, chondroitin sulfate or heparan sulfate content between involved and uninvolved skin were observed. These results suggest that abnormal metabolism of dermatan sulfate may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…In contrast to the normal epidermis and dermis and lack of inflammation originally reported, these authors describe such variable features as: thickened collagen and sclerosis (8,10,11,14,16), decreased elastic fibers (16), inflammation (13,15,18), and hypopigmentation (16). We believe that those instances exhibiting vacuolar alteration and a mononuclear infiltrate of inflammatory cells (8,9,14), actually represent morphea or APP following the lines of Blaschko, as has previously been reported (1,3,4,19,20), and not LAM. Some authors (17,21) have even suggested the reclassification of some of the patients originally reported as Blaschkolinear APP by Murphy et al (1) and Tajima et al (3).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In contrast to the normal epidermis and dermis and lack of inflammation originally reported, these authors describe such variable features as: thickened collagen and sclerosis (8,10,11,14,16), decreased elastic fibers (16), inflammation (13,15,18), and hypopigmentation (16). We believe that those instances exhibiting vacuolar alteration and a mononuclear infiltrate of inflammatory cells (8,9,14), actually represent morphea or APP following the lines of Blaschko, as has previously been reported (1,3,4,19,20), and not LAM. Some authors (17,21) have even suggested the reclassification of some of the patients originally reported as Blaschkolinear APP by Murphy et al (1) and Tajima et al (3).…”
Section: Discussionmentioning
confidence: 51%
“…The major abnormal findings in our patient are as follows: (1) congenital onset; (2) stable, slightly depressed linear plaques; (3) a lack of symptomatology or attendant malformations; and (4) subtle histopathologic changes of the affected epidermis and papillary dermis accounting for the clinical atrophy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“… 1–3 Tajima et al . 20 reported the increase of DS and total GAG content per mg dry weight in the involved skin of APP. With regard to this discrepancy, it is possible that Tajima's case was a type of APP of closely related to LSc and that our cases were APP of true unique atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that genetic factors, neurogenic cause, immunological factors, and abnormal metabolism of dermatan sulfate may play a role in the pathogenesis of IAPP. [2][3][4][5] The role of Borrelia burgdorferi remains controversial. [6] IAPP is classically thought of as an idiopathic atrophy of the dermis.…”
Section: Discussionmentioning
confidence: 99%